Psycho-Emotional Aspects of Pregnant Women Diagnosed with a Rare Disease: A Systematic Review - Celia Cortés-Martín; Juan Carlos Sánchez-García; Beatriz Piqueras-Sola; Jonathan Cortés-Martín; Andrés Reinoso-Cobo; Jose Manuel Martínez-Linares; Raquel Rodríguez-Blanque (Nursing Reports)
Background: Psycho-emotional aspects as a cross-cutting theme have gained relevance and scientific interest in recent years. Pregnant women diagnosed with a rare disease constitute a vulnerable population, experiencing psycho-emotional challenges due to their specific circumstances. It is essential that this group is informed and receives the proper to manage the physical, emotional, and psychological challenges linked to their condition. Objectives: The aim of this review is to understand how the diagnosis of a rare disease affects the psycho-emotional aspects of a pregnant woman. Methods: The research question posed is how does the diagnosis of a rare disease affect the psycho-emotional aspects of a pregnant woman? This systematic review has been carried out following the PRISMA model and has been registered in PROSPERO with registration number CRD42024558523. A literature search was conducted in the databases of Scopus, PubMed, Cinahl, Scielo, and the Cochrane Library. Articles were selected on the basis of the following inclusion criteria: publication in the last twenty years and all languages. Results: In the end, 28 articles were selected. The main results highlight that there is a negative impact on the psycho-emotional level in these patients, altering aspects such as anxiety, stress, social rejection, and self-stigma. Conclusion: The role of nursing in addressing this psycho-emotional dimension as a mediator between families and other branches of the health sciences environment stands out.